AJUDEEM!! EQUAÇÃO 1 GRAU!!
A) 3-(3x-6) = 2x+(4-x)
Soluções para a tarefa
Respondido por
0
3 - (3x - 6) = 2x + (4 - x)
3 - 3x + 6 = 2x + 4 - x
9 - 3x = x + 4
9 - 4 = x + 3x
4x = 5
x = 5/4
3 - 3x + 6 = 2x + 4 - x
9 - 3x = x + 4
9 - 4 = x + 3x
4x = 5
x = 5/4
Respondido por
2
Boa Tarde
3 - (3x - 6) = 2x + (4 - x)
3 - 3x + 6 = 2x + 4 - x
- 3x + x - 2x = 4 - 3 - 6
- 4x = - 5
x = - 5
-4
x = 5
4
Duvidas?! é só comentar
3 - (3x - 6) = 2x + (4 - x)
3 - 3x + 6 = 2x + 4 - x
- 3x + x - 2x = 4 - 3 - 6
- 4x = - 5
x = - 5
-4
x = 5
4
Duvidas?! é só comentar
Perguntas interessantes